Methodology of substantive fatigue life valuation of composite components of aero structure - V. E. Strizhius (Научный вестник МГТУ ГА)
The key features of the regulatory requirements for the fatigue life valuation of composite laminates were presented. With allowance for those requirements and through the use of the well-known patterns of residual strength degradation and stiffness degradation of layered composite materials over the course of fatigue cumulation, the fundamental principles of the methodology of substantive fatigue life valuation were created. They, in particular, can be used for the lower and upper wing paneling of the transport category of aircraft. It was indicated that it’s worth making the substantive valuation at the project definition stage of an aircraft, when the key parameters of the laminates are being determined: the type of layered composite materials, parameters of their placement, selection of analytical stresses, etc. As a conditional sample of the substantive fatigue life valuation of carbon fiber laminate, was presented to use as the AS4-PW 10/80/10 (8,84 mm thick) used in the capacity of the upper wing paneling of the transport aviation planes. The types of valuations were performed as follows: fatigue life prediction for the samples with free holes; fatigue life prediction for the samples with scarcely visible shock damages; fatigue life prediction for the samples with scarcely visible shock damages prior to reaching the standard residual strength degradation level; fatigue life prediction for the samples with scarcely visible shock damages prior to reaching the standard residual stiffness degradation level. The above valuations exposed significant distinctions between the received values for the different samples depending on the used prediction method. The analysis of the received values revealed the necessity of making the same substantive estimates for determination of the fatigue life valuation of composite components of aero structures with acceptable accuracy.